PENENTUAN SANTRI TELADAN MELALUI SISTEM PENDUKUNG KEPUTUSAN MENGGUNAKAN METODE PROFILE MATCHING (STUDI KASUS DI PONDOK PESANTREN AT-TAQWA CIREBON) - Shandy Alfian; Nana Suarna; Rini Astuti (Universitas Ma'soem, 2019)
The education system in Islamic boarding schools is one way in which students will be selected as exemplary students and given awards annually. The selection process so far has not used a computerized assessment system, so that every part that requires assessment cannot quickly get an objective result in determining the assessment of the exemplary santri. The decision support system for the exemplary santri election was an alternative solution. This decision-making system can take into account all the criteria for selecting students quickly, easily in the data processing decision making process to determine the exemplary students. The method used in the design of this system uses the profile maching method through the PHP programming language and MySQL database. From this research the hypothesis p value (sig) 0,000 <0.5 and t-count (36,982> 1,699) t-table is obtained, so H0 is rejected, Ha is accepted. so it can be concluded that the profile matching method can make it easier to determine exemplary santri.